RECOGNITION AND PRIORITY OF KEY SUCCESS FACTORS (KSF) INCUSTOMERS CLUBS AND CUSTOMERS LOYALTY PROGRAMS - Alireza Jafari; Hossein Vazifedoust; Elaheh Farhadi (European Scientific Journal, ESJ, 2015)
The present study aims to identify and prioritize the Key Success Factors (KSFs) of Customer clubs and Customer Loyalty programs, in Bank Mellat Iran. The different models of Key Success Factors from previous researchers have been studied, and according to 12 experts of bank Mellat Iran, a model of KSFs of Customer clubs and Customer Loyalty programs in banking industry, has been presented. It’s a combination of previous researches models, including 20 factors affecting the success of Bank Customer clubs and Customer Loyalty program. A questionnaire of 20 success factors have been designed for determining the effect of each factor on the other 19 factors. It has been filled by 12 experts with over 10 years of experience in banking industry. Then, it has been analyzed by Fuzzy DEMATEL method, and the research results has been extracted. This research concluded 20 main key success factors of Customer clubs and Customer Loyalty programs, in Bank Mellat Iran; the 5 fist most important success factors are in order as: 1. the seller's contact assets, 2. price, discounts and free products, 3. Lack of attention to monitoring system and continuous supervision, 4. Quality of customer services, 5. Creating value for customers.